Research and innovation processes revisited – networked responsibility in industry. Issue 3 (3rd July 2017) - Timmermans, Job; Yaghmaei, Emad; Stahl, Bernd Carsten; Brem, Alexander
Abstract : Purpose: The purpose of this paper is to explore how relationships between different actors are being shaped to allow industry to come to acceptable and desirable uses of research and innovation (R&I) that address societal challenges. Design/methodology/approach: Building on existing notions of responsibility proposed in the literature, the paper develops a theoretical account of "networks of responsibility" which capture the interlinked nature of responsibility relationships. The usefulness of the approach is evaluated by exploring two cases of R&I in industry deploying a qualitative research approach that involves interviewing and document analysis. For this, a multinational company from Germany was involved, as well as a small- and medium-sized company from Denmark. Findings: The study surfaced 68 responsibility relationships involving a range of different objects, subjects, authorities and norms. By describing overlaps in objects, subjects and other aspects across relationships, the theoretical model proved adequate in untangling and displaying interrelatedness of responsibilities. Furthermore, the analysis surfaced characteristics of responsible research and innovation (RRI) that are already in place in the R&I processes of two innovative companies, such as anticipation, foresight and stakeholder engagement. Not all aspects of responsibility outlined in the theoretical model could be extracted from the interview data for every responsibility relationship, pointing to the need for further research. Practical implications: The paper is practically relevant because it supports policy development on an organisational, as well as societal level. Moreover, the networks of responsibility model offer a fine-grained assessment of responsibilities in R&I practice by mapping existing responsibilities which supports translating RRI principles into everyday organisational practices. Social implications: RRI sets an ambitious agenda to ensure a more social and ethical R&I. Much work is still needed to bridge the gap between these theoretical and political aspirations and daily R&I practice, especially in non-academic contexts such as industry. By offering a way to understand and untangle the complexity of responsibility relationships, the networks of responsibility model seem to offer a promising approach that can support this endeavour. Originality/value: The paper offers a novel theoretical approach to understanding and analysing responsibility allocations in R&I in industry. It demonstrates the reliability of this theoretical position empirically. It is practically important because it supports policy development on an organisational as well as societal level.